From Spy to Editor – Informants of Elżbieta Sieniawska née Lubomirska (d. 1729), Wife of the Castellan of Krakow - Monika Łękawska (Knygotyra)
Research on written newspapers of the Saxon period has been ongoing for several decades. By looking at the avis from the perspective of their editors and purveyors, we get a fuller picture of the mentality of society. Elżbieta Sieniawska, née Lubomirska (d. 1729), Wife of the Castellan of Krakow and one of the most enterprising magnates at the turn of the 17th and 18th centuries, collected information through her intelligence services. Had it not been for their efforts and every attempt to provide the Krakow castellan with news, it is likely that Sieniawska would have had serious problems keeping her knowledge of the country and the world up to date. Distinguishing in the article the profiles of spies, postal workers and newspaper editors, the author shows not only previously unpublished facts from the life of the information services, but above all points to the dependencies between their services.